Fertilización de arroz de riego en el departamento del Meta. - Sánchez Sánchez, Luis Fernando; Suárez Montes, José G.; Owen Bartlett, Eric J. (Federación Nacional de Arroceros - FEDEARROZ, 2018)
Arroz-Oryza sativa